PENGEMBANGAN E-MODUL BERBASIS HEYZINE FLIPBOOK PADA PEMBELAJARAN MENULIS TEKS BIOGRAFI KELAS X - Amiyah, Walidatul (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2024)
This research is product development which aims to develop a Heyzine flipbook-based e-module for learning to write biographical texts. This heyzine flipbook based e-module is used by teachers as a tool used by teachers in delivering material. This type of method is Research and Development (R&D). The research results based on the quality and suitability of these teaching materials have been tested for validity by teaching materials experts and material experts. The validation results from the validators are that the appearance of this development is 92%, average 3.7 in the very good category, presentation aspect is 100%, average 4 in the very good category, practicality aspect is 89%, average 3.5 in the very good category, quality aspect content and objectives are 100% with a mean of 4 in the very good category, the aspect of the determination of reference materials is 92% with a mean of 3.6 in the very good category, the graphic aspect is 100% in the very good category and the aspect of language use is 95% with a mean of 3.8 with very good category. The feasibility test results show that the heyzine flipbook based e-module is very suitable for use.